2016
DOI: 10.1128/jvi.03058-15
|View full text |Cite
|
Sign up to set email alerts
|

Hepatitis B Virus Capsids Have Diverse Structural Responses to Small-Molecule Ligands Bound to the Heteroaryldihydropyrimidine Pocket

Abstract: Though the hepatitis B virus (HBV) core protein is an important participant in many aspects of the viral life cycle, its best-characterized activity is self-assembly into 240-monomer capsids. Small molecules that target core protein (core protein allosteric modulators [CpAMs]) represent a promising antiviral strategy. To better understand the structural basis of the CpAM mechanism, we determined the crystal structure of the HBV capsid in complex with HAP18. HAP18 accelerates assembly, increases protein-protein… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
88
2
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(91 citation statements)
references
References 67 publications
(141 reference statements)
0
88
2
1
Order By: Relevance
“…In the presence of BAY 41-4109, the drug induces a conformational change within the HBc dimer to promote a structural transfer from HBc Act to HBc Abb ; by weakening the inter-dimer interactions, and destabilizing the capsid thereby driving the assembly into the helical tube ensemble. Alternatively, BAY 41-4109, which is structurally similar to HAP-1 26 , could bind like HAP-1 at the hydrophobic pocket formed by helices α2, α4b and α5 of HBc and helix α5 of neighbour HBc 27, 31 . Thus BAY 41-4109 induced conformational changes of HBc, particularly the up-ward movement of helix α5, may change the dimer-dimer interaction angle and decrease the curvature of the ensemble, driving the assembly from capsid to tube.
Figure 6Schematic model of HBc assembly controlled by allosteric conformational changes.
…”
Section: Discussionmentioning
confidence: 99%
“…In the presence of BAY 41-4109, the drug induces a conformational change within the HBc dimer to promote a structural transfer from HBc Act to HBc Abb ; by weakening the inter-dimer interactions, and destabilizing the capsid thereby driving the assembly into the helical tube ensemble. Alternatively, BAY 41-4109, which is structurally similar to HAP-1 26 , could bind like HAP-1 at the hydrophobic pocket formed by helices α2, α4b and α5 of HBc and helix α5 of neighbour HBc 27, 31 . Thus BAY 41-4109 induced conformational changes of HBc, particularly the up-ward movement of helix α5, may change the dimer-dimer interaction angle and decrease the curvature of the ensemble, driving the assembly from capsid to tube.
Figure 6Schematic model of HBc assembly controlled by allosteric conformational changes.
…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, determination of the crystal structure of the HBV capsids in complex with three different HAPs demonstrated that each HAP compound induces distinct allosteric responses of core protein and results in different quaternary and tertiary structural changes of core protein subunits in assembled capsids (53). In this study, we showed that a 1.5% native agarose gel electrophoresisbased particle gel assay is a very sensitive and convenient method to reveal the alterations of assembled capsids, due to either core protein mutation or treatment of capsid assembly modulators.…”
Section: Discussionmentioning
confidence: 99%
“…In summary, the results presented in this section further support the notion that the antiviral activity of SBA and BA compounds depends solely on core protein and not polymerase. Moreover, although both SBAs and BAs modulate capsid assembly by binding to the HAP pocket, the two compounds distinctly interact with core protein and induce different structural alterations of capsids (53).…”
mentioning
confidence: 99%
“…Dengan mengganggu peran protein inti ini maka replikasi virus akan terhambat. Oleh karena itu protein inti VHB ini merupakan target yang sangat baik untuk pengembangan antivirus baru yang selektif, aman dan efektif (Bourne et al 2008;Campagna et al 2013;Klumpp et al 2015;Zlotnick et al 2015;Venkatakrishnan et al 2016). …”
Section: Pendahuluanunclassified